Efforts to Improve the Understanding of the Praiseworthy Morals of Husnuzzan, Tawadhu', Tasamuh, and Ta'awun by Implementing the Learning Together Learning Model at Mts An Najah Petaling - Iwarzah, Yupantri; Yunus; Yulianti; Yulistianingsih; Yusniawati (MANDAILING GLOBAL EDUKASIA, 2024)
This study aims to improve students' understanding of the material on Commendable Morals, which includes husnuzzan (having good thoughts), tawadhu' (humble), tasamuh (tolerance), and ta'awun (helping each other), through the application of the Learning Together (LT) learning model. The research method used is Classroom Action Research (CAR) with subjects of class VIII students of MTs An Najah Petaling, Lais District, Musi Banyuasin Regency. This study involved teachers and students as the main data sources. Data collection techniques were carried out through two approaches, namely tests and non-tests. The test approach was used to measure students' understanding before and after the application of the LT learning model, while non-test techniques were carried out through observation, interviews, and documentation to obtain supporting data related to the learning process. The results of the study are expected to show the effectiveness of the LT learning model in improving students' understanding of the material on Commendable Morals. Thus, this study contributes to the development of more interactive and collaborative learning methods in the Akidah Akhlak subject. In addition, the results of this study can be a reference for educators in implementing learning strategies that can improve students' understanding of commendable moral values ​​more effectively and comprehensively..